The impact of anorectal malformations on anorectal function and social integration in adulthood: report from a national database. (24th June 2013) - Mantoo, S.; Meurette, G.; Wyart, V.; Hardouin, J.; Cretolle, C.; Capito, C.; Sarnacki, S.; Podevin, G.; Lehur, P.‐A.
Abstract Aim The impact of anorectal malformation (ARM) on bowel function and social, educational and occupational end‐points was investigated in adult patients entered on a national database. Method Data from a national database of adult patients operated on between 1962 and 1999 for ARM were analysed. The database Malformations Ano‐rectales et Pelviennes rares (MAREP) was part of a common information system, CEMARA, on rare congenital disorders. A self‐administered questionnaire regarding bowel function, academic qualifications, employment and family status was mailed to patients. The type of ARM, subsequent follow‐up and management including surgical interventions were retrospectively retrieved from medical records. Results Of 210 adult patients on the registry since 2008, 68 were included in this study. Only three (8.5%) had had regular follow‐up. All reported some disturbance in bowel function. The fertility rate of 1.5 children per woman did not differ from the general population. Conclusion Anorectal malformation ARM often leads to suboptimal bowel function in adulthood. This has an impact on social integration.